2009
DOI: 10.1007/s11094-009-0275-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and biological activity of a fraction of meadowsweet extract

Abstract: Studies of the chemical composition of a butanol fraction of an extract from the above-ground part of the meadowsweet in 70% ethanol yielded five substances which were flavonoids (quercetin, isoquercetin, quercetin 4¢-glucoside, rutin) and phenolcarboxylic acids (gallic acid). The fraction was found to have nootropic actions, with antiamnestic, antihypoxic, antioxidant, and adaptogenic activities. Studies of the antioxidant properties of the individual compounds showed that isoquercetin, quercetin 4¢-glucoside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
0
5
0
3
Order By: Relevance
“…Because of its anti-inflammatory properties, Harbourne et al studied the phenolic content of aqueous F. ulmaria extracts for their incorporation into a beverage as a functional ingredient [2]. It has been shown that meadowsweet contains phenolic constituents such as flavonoid aglycons (e.g., quercetin, kaempferol), glycosylated flavonoids (e.g., rutin, hyperoside, quercitrin, avicularin, astragalin), and hydrolysable tannins (tellimagrandin I and II, rugosin A, B, D, and E) as well as salicylates (salicylic acid, methyl salicylate, salicylaldehyde, salicylalcohol and their glycosides) [3][4][5][6][7][8][9]. Only a limited number of non-phenolic constituents such as phytosterols, carotenoids, triterpenes, and chlorophyll derivatives have been reported [7,10,11].…”
mentioning
confidence: 99%
“…Because of its anti-inflammatory properties, Harbourne et al studied the phenolic content of aqueous F. ulmaria extracts for their incorporation into a beverage as a functional ingredient [2]. It has been shown that meadowsweet contains phenolic constituents such as flavonoid aglycons (e.g., quercetin, kaempferol), glycosylated flavonoids (e.g., rutin, hyperoside, quercitrin, avicularin, astragalin), and hydrolysable tannins (tellimagrandin I and II, rugosin A, B, D, and E) as well as salicylates (salicylic acid, methyl salicylate, salicylaldehyde, salicylalcohol and their glycosides) [3][4][5][6][7][8][9]. Only a limited number of non-phenolic constituents such as phytosterols, carotenoids, triterpenes, and chlorophyll derivatives have been reported [7,10,11].…”
mentioning
confidence: 99%
“…Meanwhile, FRAP assay showed the antioxidant ability of polysaccharides in the plant extracts react with a colorless Fe(III) to generate a colored Fe(II)-tripyridyltriazine form which can measured at 593 nm absorbance. A number of in-vitro antioxidant studies has been carried out including TEAC, Oxygen Radical Absorbance Capacity (ORAC) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging shown antioxidant activity potential in the AV and FU extracts [15,30,31]. However, to the best of our knowledge this is the first report of antioxidant activity extract from AV and FU assessed using FRAP method.…”
Section: Results and Discussion Extraction Yield Total Polyphenols Amentioning
confidence: 99%
“…Àíòèîêñèäàíòíóþ àêòèâíîñòü îòâàðîâ ñáîðîâ in vitro èçó÷àëè ìåòîäîì êàòîäíîé âîëüòàìïåðîìåòðèè ñ èñïîëüçîâàíèåì àíàëèçàòîðà ÀÎÀ-1 (Ïîëèàíò, Òîìñê). Àíòèîêñèäàíòû (ÀÎ), èìåþùèå âîññòàíîâèòåëüíóþ ïðèðîäó, âçàèìîäåéñòâóþò ñ êèñëîðîäîì, åãî àêòèâíûìè ðàäèêàëàìè è óìåíüøàþò êàòîäíûé òîê ýëåêòðîâîññòàíîâëåíèÿ êèñëîðîäà íà ðòóòíî-ïëåíî÷íîì ýëåêòðîäå â îáëàñòè ïîòåíöèàëîâ îò 0 äî (-0,6)  [4,7,9].  êà÷åñòâå ôîíîâîãî ýëåêòðîëèòà èñïîëüçîâàëè ôîñôàòíûé áóôåð pH 6,86 (10 ìë) äëÿ âîäíî-ýòàíîëüíûõ ðàñòâîðîâ.…”
Section: ýêñïåðèìåíòàëüíàÿ ÷àñòüunclassified
“…Ñ ó÷åòîì ïðèñóòñòâèÿ ðàçíîîáðàçíûõ ôåíîëüíûõ ñîåäèíåíèé â èíãðåäèåíòàõ [3,4,7,8] ñáîðîâ íàìè îñóùåñòâëåíî èññëåäîâàíèå àíòèîêñèäàíòíûõ ñâîéñòâ èõ îòâàðîâ. Ïåðâîíà÷àëüíî äëÿ ýòîãî èçó÷àëè âçàèìîäåéñòâèå ÁÀ îòâàðîâ ñ êèñëîðîäîì è ðàäèêàëüíûìè ïðîäóêòàìè åãî âîññòàíîâëåíèÿ in vitro ñ ïîìîùüþ ìåòîäà êàòîäíîé âîëüòàìïåðîìåòðèè, â îñíîâå êîòîðîãî ëåaeèò ìîäåëüíàÿ ðåàêöèÿ ýëåêòðîâîññòàíîâëåíèÿ êèñëîðîäà, ïðîòåêàþùàÿ íà ýëåêòðîäå ïî ìåõàíèçìó, àíàëîãè÷íîìó âîññòàíîâëåíèþ êèñëîðîäà â òêàíÿõ è êëåòêàõ îðãàíèçìà ÷åëîâåêà [9].…”
Section: ðåçóëüòàòû è èõ îáñóAeäåíèåunclassified
See 1 more Smart Citation